2017
DOI: 10.1111/anae.14062
|View full text |Cite
|
Sign up to set email alerts
|

Defining sepsis on the wards: results of a multi‐centre point‐prevalence study comparing two sepsis definitions

Abstract: Our aim was to prospectively determine the predictive capabilities of SEPSIS-1 and SEPSIS-3 definitions in the emergency departments and general wards. Patients with National Early Warning Score (NEWS) of 3 or above and suspected or proven infection were enrolled over a 24-h period in 13 Welsh hospitals. The primary outcome measure was mortality within 30 days. Out of the 5422 patients screened, 431 fulfilled inclusion criteria and 380 (88%) were recruited. Using the SEPSIS-1 definition, 212 patients had sepsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
62
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 33 publications
10
62
1
1
Order By: Relevance
“…The acuity of the cohort was high as NEWS 7 or higher indicates the need for prompt assessment by a clinical team with critical care competencies and consideration for transfer of the patient to a higher‐dependency care area (McGinley and Pearse, ). Similar NEWS scores were observed in recent US and UK studies, including ours (Churpek et al, ; Corfield et al, ; Szakmany et al, ; Szakmany et al, ). Importantly, 91% of the patients appeared to respond favourably to the Sepsis Six, and only six patients had an increase in their NEWS within 24 h of treatment.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The acuity of the cohort was high as NEWS 7 or higher indicates the need for prompt assessment by a clinical team with critical care competencies and consideration for transfer of the patient to a higher‐dependency care area (McGinley and Pearse, ). Similar NEWS scores were observed in recent US and UK studies, including ours (Churpek et al, ; Corfield et al, ; Szakmany et al, ; Szakmany et al, ). Importantly, 91% of the patients appeared to respond favourably to the Sepsis Six, and only six patients had an increase in their NEWS within 24 h of treatment.…”
Section: Discussionsupporting
confidence: 90%
“…Baseline data on compliance with the Sepsis Six was 34% for all patients who were admitted to the ICU with sepsis in 2011 (local audit). Data from our collaborative studies from every Welsh hospital confirmed that this is not an isolated problem: we found that only 24 of 290 patients who fulfilled the sepsis criteria were seen by the CCOT in 2015, and this did not improve in 2016 (Szakmany et al, , ). Based on these figures, we estimate that, at the beginning of our observation period, there were at least thrice as many patients with sepsis on the wards compared with the ones seen by the CCOT.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In this meta-analysis, 35 studies with 269,544 patients reported on the prognostic accuracy of the qSOFA and short-term mortality, including 27 retrospective studies [5][6][7][8]10,11,[13][14][15][16]18,20,22,[24][25][26][27]29,[32][33][34][35][37][38][39][40] , while 8 studies were prospective studies 9,12,17,19,21,23,28,30,36 . Due to the heterogeneity of the inclusion criteria, a random-effects model was used to calculate the pooled sensitivity and specificity of the included studies.…”
Section: The Qsofa and Short-term Mortalitymentioning
confidence: 99%
“…Sepsis is described as "life-threatening organ dysfunction caused by a dysregulated host response to infection, " leading to injury to healthy tissues, including those remote to the infection site (1,2) and is part of a systemic inflammatory response syndrome group of conditions which can be infectious or non-infectious in origin. This can then progress to organ failure (such as acute kidney and acute lung injury) and septic shock if there is additional cardiovascular system involvement (3).…”
Section: Introductionmentioning
confidence: 99%